ERAS implementation in an urban patient population undergoing gynecologic surgery. (December 2022) - Brown, Morgan L.; Simpson, Vidda; Clark, Annabelle B.; Matossian, Margarite D.; Holman, Stacey L.; Jernigan, Amelia Marie; Scheib, Stacey A.; Shank, Jessica; Key, Alison; Chapple, Andrew G.; Kelly, Elizabeth; Nair, Navya
Abstract: Background: Enhanced recovery after surgery (ERAS) protocols improve outcomes. We investigated ERAS implementation in a population with comorbid conditions, inadequate insurance, and barriers to healthcare undergoing gynecologic surgery. Objective: To investigate ERAS implementation in publicly insured/uninsured patients undergoing gynecologic surgery on hospital length of stay (LOS), 30-day hospital readmission rates, opioid administration, and pain scores. Study design: Data were obtained pre- and post-ERAS implementation. Patients undergoing gynecologic surgery with private insurance, public insurance, and uninsured were included (N = 589). LOS, readmission <30 days, opioid administration, and pain scores were assessed. Results: Implementation of ERAS led to shorter LOS 1.75 vs. 1.49 days (p = 0.008). Average pain scores decreased from 3.07 pre-ERAS vs. 2.47 post-ERAS (p = <0.001). Opioid use decreased for ERAS patients (67.22 vs. 33.18, p = <0.001). Hospital readmission rates were unchanged from 8.2% pre-ERAS vs. 10.3% post-ERAS (p = 0.392). Conclusions: ERAS decreased pain scores and opioid use without increasing LOS or readmissions. Highlights: Enhanced Recovery After Surgery protocols improve outcomes. ERAS is safe and effective in uninsured/publicly insured population. ERAS implementation resulted in decreased opioid use, pain scores, and LOS. ERAS implementation did not increase hospital readmission rates.